Selected health characteristics are associated with urban Canadians’ acceptability of policies promoting healthier restaurant food environments - Jessica Lambert-De Francesch; Kadia Saint-Onge; Nazeem Muhajarine; Lise Gauvin (Public Health Nutrition)
Abstract